The story of my life - Keller, Helen (New York Watermill Press, 1993)
Helen Keller's personal recollections and correspondence reveal her relationship with her beloved teacher, Annie Sullivan, and the problems and obstacles she encountered as she struggled to overcome her handicaps
Keywords: Tham khảo